Evaluation of Local Site Amplification in Lima, Peru using Earthquake Ground Motion Records - Quispe Gamero, Mileyvi Selene (2015)
Descargue el texto completo en el repositorio institucional de la Tokyo Institute of Technology: https://ci.nii.ac.jp/naid/500000965617